Distance to Opportunity: Higher Education Deserts and College Enrollment Choices - Riley Acton; Kalena E. Cortes; Camila Morales (Institute of Labor Economics (IZA), 2024)
We study how geographic access to public postsecondary institutions is associated with students' college enrollment decisions across race and socioeconomic status. Leveraging rich administrative data, we first document substantial differences in students' local college options, with White, Hispanic, and rural students having, on average, many fewer nearby options than their Black, Asian, suburban, and urban peers. We then show that students are sensitive to the distance they must travel to access public colleges and universities, but there are heterogeneous effects across students. In particular, we find that White and non-economically disadvantaged students respond to living far from public two-year colleges primarily by enrolling in four-year colleges, whereas Black, Hispanic, and economically disadvantaged students respond primarily by forgoing college enrollment altogether. Lastly, in a series of decomposition and simulation exercises to inform public policy efforts to increase college enrollment, especially among underrepresented minorities and low-income students, we find that differences in students' sensitivity to distance, rather than differences in distance to the nearest college, primarily contribute to observed four-year college enrollment gaps across racial and ethnic groups.
Keywords: I21; I23; I24; 330; college proximity; college accessibility; college choices; college enrollment; two-year colleges; four-year colleges; public postsecondary institutions